Adsorption Characteristics of Selected Dyes Using Activated Carbon Derived from Piliostigma thonningii (Fabaceae: Cercidoideae) Stem - Mohammed, Mustapha Bala; Abubakar, Suwaida; Isah, Maryam Shika (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Adsorption characteristics include the initial dye concentration effect, flow rate and adsorbent dose of dyes using activated Piliostigma thonningii Charcoal (PTC) were studied. The adsorption process of the dyes was done using column chromatographic technique at constant temperature and fixed pH of the dye’s concentration. Optimization of the column adsorption parameters was conducted, and the maximum percentage removal was attained through setting the level of variables of the adsorption process to initial 100mg/L MB and BM dye concentrations, 30ppm MD dyes and a flow rate of 3mL/min. With lower initial concentration, higher bed height of the adsorbent and lower feed flow rate, the performance of the fixed-bed adsorption system was found to be better. With the highest bed height of 28cm (10g adsorbent dose), maximum adsorption capacity was achieved. The research can help in recycling the wastewater discharged by the textile industries, which will help in reducing the level of water scarcity for industrial use.